Advanced Imaging Modalities in the Detection of Cerebral Vasospasm. (6th February 2013) - Mills, Jena N.; Mehta, Vivek; Russin, Jonathan; Amar, Arun P.; Rajamohan, Anandh; Mack, William J.
Abstract : The pathophysiology of cerebral vasospasm following aneurysmal subarachnoid hemorrhage (SAH) is complex and is not entirely understood. Mechanistic insights have been gained through advances in the capabilities of diagnostic imaging. Core techniques have focused on the assessment of vessel caliber, tissue metabolism, and/or regional perfusion parameters. Advances in imaging have provided clinicians with a multifaceted approach to assist in the detection of cerebral vasospasm and the diagnosis of delayed ischemic neurologic deficits (DIND). However, a single test or algorithm with broad efficacy remains elusive. This paper examines both anatomical and physiological imaging modalities applicable to post-SAH vasospasm and offers a historical background. We consider cerebral blood flow velocities measured by Transcranial Doppler Ultrasonography (TCD). Structural imaging techniques, including catheter-based Digital Subtraction Angiography (DSA), CT Angiography (CTA), and MR Angiography (MRA), are reviewed. We examine physiologic assessment by PET, HMPAO SPECT, 133 Xe Clearance, Xenon-Enhanced CT (Xe/CT), Perfusion CT (PCT), and Diffusion-Weighted/MR Perfusion Imaging. Comparative advantages and limitations are discussed.